EVALUATION OF NURSES’ KNOWLEDGE AND PRACTICES REGARDING TRACHEOSTOMY CARE: AN ANALYTICAL CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Objective: To assess the knowledge and practices of nurses regarding the care of patients who have undergone tracheostomy.Methods: This cross-sectional study, conducted from January to June 2024 at Kishwar Fazal Teaching Hospital, Sheikhupura assessed 80 nurses' tracheostomy care knowledge and practices using a detailed questionnaire. Participants were selected based on convenience sampling. Chi-square test, independent sample t-test, and ANOVA test were used to analyze the association between demographic variables and the knowledge and practices of nurses regarding tracheostomy care.Results: During the study, 80 nurses were recruited. 82.5% were females and 17.5% were males, with 35% of the population under the age of 25 years. 48.8% of the nurses were graduates with a majority (27.5%) having experience ranging from 5 to 10 years. It was found that 88.75% of nurses had satisfactory knowledge, and 93.61% had satisfactory practices regarding tracheostomy care. However, 55% of the nurses had poor knowledge about the management of tracheostomized patients. There was a significant relationship between years of experience and knowledge regarding tracheostomy care.Conclusion: Nurses' performance and knowledge regarding tracheostomy care were satisfactory. However, knowledge regarding the management of tracheostomy patients was unsatisfactory. Further research with larger samples and simulation-based assessments is recommended to better evaluate the knowledge and performance of nurses regarding tracheostomy care.